Automobile transport and armored car military units of the Russian Imperial Army. 1896–1917s - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
At the end of the 19th and the beginning of the 20th century a rapid process of preparation for the war of the countries of the Triple Alliance and the Triple Entente took place, which was accompanied by an the increase in the size of the army, equipping them with automatic firearms, rapid-fire artillery and aircraft. An important element of preparation for war was the increase in the mobility of armies, in addition to horse-drawn and rail transport, automobiles began to appear. The importance of which for intelligence, transmission of reports, transportation of weapons, ammunition, personnel and food was increasingly recognized by the military leadership. The appearance of cars equipped with artillery and machine guns and later protected by armor began a new development in the ground forces. But the possibility of equipping armies with cars depended heavily on the development of industry in the state, as well as on the ability to train a sufficient number of officers and privates for automobile transport and armored car units. This article will tell from the experience of the Russian Imperial Army in automobilization